Calix[n]arene/Pillar[n]arene-Functionalized Graphene Nanocomposites and Their Applications - Duan, Qunpeng; Wang, Lijie; Wang, Fei; Zhang, Hongsong; Lu, Kui (Frontiers in Chemistry, 2020)
Calix[n]arenes and pillar[n]arenes, which contain repeating units of phenol and methane, are class of synthetic cyclic supramolecules. Their rigid structure, tunable cavity size, flexible functionalization, and rich host-guest properties make them ideal surface modifiers to construct functional hybrid materials. Introduction of the calix[n]arene/pillar[n]arene species to the graphene may bring new interesting or enhanced physicochemical/biological properties by combining their individual characteristics. Reported methods for the surface modification of graphene with calix[n]arene/pillar[n]arene utilize either covalent or non-covalent approaches. This mini-review presents the recent advancements in the functionalization of graphene nanomaterials with calix[n]arene/pillar[n]arene and their applications. At the end, the future outlook and challenges for the continued research of calix[n]arene/pillar[n]arene-functionalized graphene nanohybrids in the development of applied nanoscience are thoroughly discussed.